La-doped hafnium oxide-based ferroelectric film, capacitor and preparation method thereof

By epitaxially growing La doped hafnium oxide-based ferroelectric films on (111) orientation perovskite substrates, the problems of traditional ferroelectric films in polarization fatigue, coercive field and growth quality are solved, high residual polarization, low coercive field and good fatigue resistance are achieved, and the service life and energy efficiency of the device are improved.

CN119815842AActive Publication Date: 2025-04-11NANJING UNIV

Patent Information

Application Number
CN202510276203.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-04-11
Estimated Expiration
2045-03-10

AI Technical Summary

Technical Problem

Traditional Zr element-doped hafnium oxide-based ferroelectric films have serious polarization fatigue, high coercive field and poor growth quality on (111) oriented perovskite substrates.

Method used

The La doped hafnium oxide-based ferroelectric film is used to epitaxially grow on a perovskite substrate oriented (111). Through suitable La doping concentration and growth conditions, high residual polarization, low coercive field and good fatigue resistance are achieved.

Benefits of technology

A high-quality La doped hafnium oxide-based ferroelectric film is achieved on (111) oriented perovskite substrates, with lower coercive fields and better fatigue properties, extending the service life of the material and reducing the energy consumption of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119815842A_ABST
    Figure CN119815842A_ABST
Patent Text Reader

Abstract

The invention discloses a La-doped hafnium oxide-based ferroelectric film, a capacitor and a preparation method of the La-doped hafnium oxide-based ferroelectric film, the La-doped hafnium oxide-based ferroelectric film is of a single (111)-oriented orthorhombic phase structure, and the preparation method comprises the following steps: firstly, epitaxially growing a buffer layer with consistent orientation on a (111)-oriented perovskite substrate, and then epitaxially growing a La-doped hafnium oxide-based ferroelectric film layer on the surface of the buffer layer. The La-doped hafnium oxide-based ferroelectric thin film is obtained by the method, the thickness of the thin film is accurately regulated and controlled, the performance of the La-doped hafnium oxide-based ferroelectric thin film is optimized, and the requirement of an electronic device for a high-performance ferroelectric thin film is met. The laser pulse deposition epitaxial La-doped hafnium oxide-based ferroelectric film provided by the invention is high in purity and good in film forming uniformity; meanwhile, the operation process is simple, low in energy consumption, free of pollution and easy to industrialize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of semiconductors, and in particular relates to a La-doped hafnium oxide-based ferroelectric film, a capacitor and a preparation method thereof. Background Art

[0002] As the semiconductor industry accelerates its evolution towards high integration and low power consumption, the massive storage demand driven by artificial intelligence and big data places stringent requirements on the CMOS compatibility and three-dimensional integration capabilities of storage devices. Ferroelectric memory has become a research hotspot due to its advantages such as non-volatility, high-speed read / write, and low power consumption, but the compatibility issues between traditional ferroelectric materials and complementary metal oxide semiconductor CMOS processes restrict its application. HfO2-based films themselves have high-K properties and are used as dielectric materials. Since the first report of Si:HfO2 ferroelectric films in 2011, hafnium oxide-based ferroelectrics have attracted much attention due to their compatibility with CMOS processes, and have made many breakthroughs in their applications in semiconductor electronic devices such as ferroelectric random access memory (FeRAM), ferroelectric field effect transistors (FeFET), and ferroelectric tunnel junctions (FTJ).

[0003] In recent years, epitaxial growth technology has provided a key path for the performance optimization of HfO2-based ferroelectric films: through heteroepitaxial strain engineering, the metastable orthorhombic phase of the film can be precisely controlled, significantly improving its polarization stability. The research focus has shifted from polycrystalline films to single-crystal epitaxial systems. The current mainstream research focuses on Zr-doped hafnium oxide-based ferroelectric films. However, these films generally have some problems that need to be solved: First, there is a serious polarization fatigue dilemma. With the increase in the number of uses, the polarization performance of the material declines sharply, which greatly shortens the service life of the material and limits the long-term stable operation of related devices; second, taking the traditional HZO (zirconium-doped hafnium oxide) system as an example, its coercive field is relatively high, which leads to the need to consume more energy to achieve polarization reversal during device operation, resulting in higher energy consumption, and exploring new doping systems to reduce the coercive field and reduce energy consumption has become a top priority; third, in terms of substrate selection, the current mainstream research mostly uses perovskite (001) and (110) oriented substrates, and the research on (111) oriented perovskite substrates is still in its infancy. Although the exploration of (111)-oriented substrates has been launched, the experimental results show that the quality of the grown ferroelectric hafnium oxide-based films is poor, multiple crystal systems appear in the films, it is difficult to obtain high-quality films with a single (111) orientation, and there is still the dilemma of polarization fatigue. At the same time, because the growth conditions are difficult to control accurately, different doping elements and concentrations will cause the lattice constant of the ferroelectric hafnium oxide film to be incompatible with the (111)-oriented perovskite substrate, which in turn affects the growth quality and orientation consistency of the film. Summary of the invention

[0004] Purpose of the invention: The first purpose of the present invention is to provide a La-doped hafnium oxide-based ferroelectric film epitaxially grown on a (111)-oriented perovskite substrate with high remnant polarization, low coercive field and good fatigue resistance; the second purpose of the present invention is to provide a method for preparing the film, accurately control the film thickness, optimize the performance of the La-doped hafnium oxide-based ferroelectric film, and meet the needs of electronic devices for high-performance ferroelectric films; the third purpose of the present invention is to provide a La-doped hafnium oxide-based ferroelectric film capacitor and a preparation method thereof.

[0005] Technical solution: The La-doped hafnium oxide-based ferroelectric thin film of the present invention is an orthorhombic phase structure with a single (111) orientation.

[0006] Preferably, the La doping concentration of the La-doped hafnium oxide is 2 to 8 at%.

[0007] More preferably, the La doping concentration of the La-doped hafnium oxide is 5 at %.

[0008] Preferably, the thickness of the La-doped hafnium oxide-based ferroelectric thin film is 10 nm to 20 nm.

[0009] The La-doped hafnium oxide-based ferroelectric film capacitor of the present invention comprises a buffer layer, a La-doped hafnium oxide-based ferroelectric film, and a metal top electrode; the buffer layer is provided with a La-doped hafnium oxide-based ferroelectric film, and the La-doped hafnium oxide-based ferroelectric film is provided with a metal top electrode.

[0010] Further preferably, the metal top electrode is a Pt top electrode, an Au top electrode or an Ag top electrode.

[0011] Further preferably, the metal top electrode is a Pt top electrode.

[0012] Preferably, the buffer layer is La (1-x) A x MnO3, 0<x<1, A is a divalent metal ion.

[0013] More preferably, A is Sr, Ca or Ba.

[0014] More preferably, the buffer layer is La 0.67 Sr 0.33 MnO3 (LSMO) or La 0.67 Ca 0.33 MnO3 (LCMO).

[0015] Preferably, the buffer layer has a thickness of 15-20 nm, and the metal top electrode has a thickness of 30-50 nm.

[0016] Further preferably, the thickness of the metal top electrode is 40 nm.

[0017] The preparation method of the La-doped hafnium oxide-based ferroelectric thin film of the present invention comprises the following steps: firstly epitaxially growing a buffer layer with a consistent orientation on a (111)-oriented perovskite substrate, and then epitaxially growing a La-doped hafnium oxide-based ferroelectric thin film layer on the surface of the buffer layer to obtain a La-doped hafnium oxide-based ferroelectric thin film.

[0018] Preferably, the (111) oriented perovskite substrate comprises SrTiO3, GdScO3 or LaAlO3.

[0019] Further preferably, the (111) oriented perovskite substrate is SrTiO3.

[0020] Further preferably, the thickness of the (111) oriented perovskite substrate is 0.3-0.7 mm.

[0021] Further preferably, the thickness of the (111) oriented perovskite substrate is 0.5 mm.

[0022] Preferably, the buffer layer is La (1-x) A x MnO3, 0<x<1, A is a divalent metal ion.

[0023] More preferably, A is Sr, Ca or Ba.

[0024] More preferably, the buffer layer is La 0.67 Sr 0.33 MnO3 (LSMO) or La 0.67 Ca 0.33 MnO3 (LCMO).

[0025] Preferably, the method for preparing the La-doped hafnium oxide-based ferroelectric thin film of the present invention comprises the following steps: (1) La-doped hafnium oxide-based target and buffer layer target are sintered by solid phase reaction method, and the target is placed in the target chamber in the growth chamber of the laser pulse deposition instrument; (2) Fixing the (111) oriented perovskite substrate on the sample stage, and placing the sample stage into the sample delivery chamber, evacuating the growth chamber and the sample delivery chamber, and then transferring the sample stage from the sample delivery chamber into the growth chamber; (3) Raise the temperature of the (111) oriented perovskite substrate to 720-780°C and use a baffle to separate the target material and the substrate; when the temperature reaches 320-380°C, introduce O2 to make the pressure in the growth chamber reach 3-7 mtorr; (4) Pre-sputtering of La-doped hafnium oxide-based target and buffer layer target; (5) After the pre-sputtering is completed, the baffle is opened. After the temperature is heated to 720~780℃, the O2 flow rate is increased to make the gas pressure in the growth chamber reach 90~110mtorr. The buffer layer is first deposited on the substrate, and the sputtering times are set to 2500~3500pulse. After the sputtering is completed, the temperature is raised to 750~810℃, and the La-doped hafnium oxide-based thin film layer is deposited, and the sputtering times are set to 2000~4000pulse. After the deposition is completed, the sample is cooled to room temperature, and the O2 pressure is maintained at 90~110mtorr during the cooling process. A La-doped hafnium oxide-based ferroelectric thin film is obtained.

[0026] Further preferably, the method for preparing the La-doped hafnium oxide-based ferroelectric thin film of the present invention comprises the following steps: (1) La-doped hafnium oxide-based target and buffer layer target are sintered by solid phase reaction method, and the target is placed in the target chamber in the growth chamber of the laser pulse deposition instrument; (2) Fixing the (111) oriented perovskite substrate on the sample stage, and placing the sample stage into the sample delivery chamber, evacuating the growth chamber and the sample delivery chamber, and then transferring the sample stage from the sample delivery chamber into the growth chamber; (3) Heating the (111) oriented perovskite substrate to 720-780°C at a rate of 3-7°C / min, and using a baffle to separate the target material and the substrate; when the temperature reaches 320-380°C, introducing O2 to make the pressure in the growth chamber reach 3-7 mtorr; (4) Pre-sputtering of La-doped hafnium oxide-based target and buffer layer target; (5) After the pre-sputtering is completed, the baffle is opened. After the temperature is heated to 720~780℃, the O2 flow rate is increased to make the gas pressure in the growth chamber reach 90~110mtorr. The buffer layer is first deposited on the substrate, and the sputtering times are set to 2500~3500pulse. After the sputtering is completed, the temperature is raised to 750~810℃ at a rate of 3~7℃ / min, and the La-doped hafnium oxide-based thin film layer is deposited, and the sputtering times are set to 2000~4000pulse. After the deposition is completed, the sample is cooled to room temperature at a rate of 3~7℃ / min. During the cooling process, the O2 pressure is maintained at 90~110mtorr. A La-doped hafnium oxide-based ferroelectric thin film is obtained.

[0027] Further preferably, the method for preparing the La-doped hafnium oxide-based ferroelectric thin film of the present invention comprises the following steps: (1) La-doped hafnium oxide-based target and buffer layer target are sintered by solid phase reaction method, and the target is placed in the target chamber in the growth chamber of the laser pulse deposition instrument; (2) Fix the (111) oriented perovskite substrate on the sample stage, place the sample stage into the sample delivery chamber, and evacuate the growth chamber and the sample delivery chamber to 5×10 -6 mbar, the sample stage is sent from the sample delivery chamber into the growth chamber; (3) The (111) oriented perovskite substrate was heated to 750°C at a rate of 5°C / min, and a baffle was used to separate the target material and the substrate; when the temperature reached 350°C, O2 was introduced to make the pressure in the growth chamber reach 5 mtorr; (4) Pre-sputtering of La-doped hafnium oxide-based target and buffer layer target; (5) After the pre-sputtering is completed, the baffle is opened. After the temperature is heated to 750°C, the O2 flow rate is increased to make the gas pressure in the growth chamber reach 100 mtorr. A buffer layer is first deposited on the substrate, and the sputtering number is set to 3000 pulses. After the sputtering is completed, the temperature is raised to 780°C at a rate of 5°C / min to deposit a La-doped hafnium oxide-based thin film layer, and the sputtering number is set to 3000 pulses. After the deposition is completed, the sample is cooled to room temperature at a rate of 5°C / min. During the cooling process, the O2 pressure is maintained at 100 mtorr. A La-doped hafnium oxide-based ferroelectric thin film is obtained.

[0028] Further preferably, in step (2), the (111) oriented perovskite substrate needs to be cleaned before being fixed on the sample stage, and the (111) oriented perovskite substrate is cleaned ultrasonically with anhydrous ethanol.

[0029] Further preferably, after cooling to room temperature in step (5), the introduction of O2 is cut off, and after the molecular pump in the growth chamber pumps out the residual O2, the growth chamber and the sample delivery chamber are connected, the sample stage is taken out to the sample delivery chamber, and after the passage between the growth chamber and the sample delivery chamber is cut off, the vacuum in the sample delivery chamber is broken and the sample stage is taken out.

[0030] The preparation method of the La-doped hafnium oxide-based ferroelectric film capacitor of the present invention comprises the following steps: firstly epitaxially growing a buffer layer with a consistent orientation on a (111)-oriented perovskite substrate, then epitaxially growing a La-doped hafnium oxide-based ferroelectric film layer on the surface of the buffer layer, covering the surface of the La-doped hafnium oxide-based ferroelectric film layer with a mask plate, magnetron sputtering a metal target, forming a metal top electrode, and obtaining a La-doped hafnium oxide-based ferroelectric film capacitor.

[0031] More preferably, the sputtering time is 8 to 12 minutes.

[0032] More preferably, the sputtering time is 10 min.

[0033] Principle of the invention: A La-doped hafnium oxide-based HfO2 film HLO with (111) orientation is epitaxially grown on a (111) oriented perovskite substrate, and it is clarified that the growth orientation of the film on this substrate is controlled by the surface energy. In addition, appropriate La doping can significantly reduce the nucleation barrier and domain wall mobility, thereby reducing the coercive field. It is also found that there is rhombus distortion in the HLO film. This distortion comes from the flexural deformation effect caused by the doping of La elements, which can stabilize the metastable ferroelectric orthorhombic phase and prevent the transformation of the orthorhombic phase to the monoclinic phase. Combined with a lower coercive field, it optimizes fatigue performance and enhances service life.

[0034] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: The present invention epitaxially grows a (111) oriented La-doped hafnium oxide-based thin film HLO on a (111) oriented perovskite substrate, which is a beneficial supplement to the experimental growth conditions and methods in the relevant field. HLO films of appropriate thickness exhibit good ferroelectric properties. The residual polarization of a 10nm film can reach 13μC / cm², and the coercive field is 2.1MV / cm; the residual polarization of a 15nm film is 11μC / cm², and the coercive field is 1.9MV / cm; the residual polarization of a 20nm film is 10μC / cm², and the coercive field is 1.7MV / cm, which are all smaller than HZO films of the same thickness. In terms of fatigue performance, the 10nm, 15nm, and 20nm thick HLO films have a 10 9 After the first cycle, the residual polarization can still be maintained at more than 80%, 74% and 68%, which is significantly better than the HZO film of the same thickness. The lower coercive field and better fatigue performance have a positive impact on reducing energy consumption, saving costs and improving the service life of devices in ferroelectric memory. The laser pulse deposition epitaxial HLO ferroelectric film proposed by the present invention has high purity and good film uniformity; at the same time, the operation process is simple, energy consumption is low, pollution-free and easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is an operational flow chart of the preparation method of Example 1 of the present invention.

[0036] Figure 2 This is a flow chart for preparing La-doped hafnium oxide-based ferroelectric capacitors according to Example 1 of the present invention.

[0037] Figure 3 This is a schematic diagram of the target material sintering temperature in Example 1 of the present invention.

[0038] Figure 4 This is the XRD q-2q spectrum of the La-doped hafnium oxide-based ferroelectric thin film in Example 1 of the present invention.

[0039] Figure 5 This is the XRD q-2q spectrum of {111} diffraction of the La-doped hafnium oxide-based ferroelectric thin film in Example 1 of the present invention.

[0040] Figure 6 This is an AFM morphology image of the La-doped hafnium oxide-based ferroelectric thin film in Example 1 of the present invention.

[0041] Figure 7 This is the hysteresis loop of the La-doped hafnium oxide-based ferroelectric thin film in Example 1 of the present invention.

[0042] Figure 8 This is the leakage current curve of the La-doped hafnium oxide-based ferroelectric film in Example 1 of the present invention.

[0043] Fig. 9 This is a fatigue endurance cycle diagram of the La-doped hafnium oxide-based ferroelectric film in Example 1 of the present invention.

[0044] Fig.10 This is a polarization state diagram of the La-doped hafnium oxide-based ferroelectric film under different cycle periods in Example 1 of the present invention. DETAILED DESCRIPTION

[0045] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0046] Example 1

[0047] Example 1 provides Figure 1-2 The method for preparing the La-doped HfO2 ferroelectric film and the capacitor thereof on the (111) oriented SrTiO3 substrate specifically comprises the following steps: In the first step, 5% La:HfO2 target and La are sintered by solid phase reaction method. 0.67 Sr 0.33 MO3 target material, and place the target material into the target material chamber in the growth chamber.

[0048] Specifically, in the first step of the solid phase reaction method to sinter the target material, the powder raw materials are first calculated and weighed, and then the raw materials are ground and mixed. After sufficient grinding and mixing, the powder is pre-sintered for 11 hours (including temperature rise and fall), and then the pre-sintered powder is pressed into tablets, and the formed target material is sintered again for 19 hours (including temperature rise and fall). The specific method is as follows: A1, calculate the amount of powder. The raw materials selected are HfO2 and La2O3 powders with a purity of 99.99%. The amount of the two powders is calculated in advance based on the target total mass of 15g and the atomic ratio Hf:La=19:1.

[0049] A2, weigh the powders. Clear a clean area on the desktop and prepare an analytical balance. The first weighing should be about 20% more than the required mass. The weighed powders are placed in an oven at 150°C for 2 hours to dry out the moisture in the powders to prevent unnecessary side reactions in subsequent reactions. After drying, perform a second measurement and weigh the two powders according to the calculated required mass.

[0050] A3, Grinding, pour the accurately weighed powder into a mortar and grind for 5 hours to ensure that the larger particles in the powder are ground into fine small particles and fully mixed together, thereby increasing the contact area of ​​the reaction and improving the reaction efficiency.

[0051] A4, pour the ground powder into a corundum crucible, seal the crucible and put it into a box-type muffle furnace according to Figure 3 The pre-sintering temperature rise and fall steps shown are used for pre-sintering. On the one hand, powder pre-sintering can make the powder particles initially connected, help atomic diffusion, and promote the formation of the corresponding HLO solid solution during the final sintering. On the other hand, it can effectively remove moisture and gases such as carbon dioxide in the raw materials, reduce the volume shrinkage of the target material during the final sintering, and play a positive role in preventing the target material from cracking and being affected by moisture.

[0052] A5, powder tableting, pour the pre-sintered powder into a mortar and grind for half an hour. After the powder returns to a uniformly mixed small particle state, put it into a cylindrical tableting mold with a diameter of 25mm, and use a manual powder tablet press to press it into a cylindrical target. The manual powder tablet press press is pressurized to 20MPa (without adding adhesive and the pressure required for HLO target is relatively high), and the pressure is maintained for 10 minutes. The powder tableting is considered successful when it is formed and there is no obvious looseness.

[0053] A6, target sintering, put the pressed target into a crucible, place it in a box-type muffle furnace, and Figure 3 The final sintering step is performed. During the sintering process, the heating rate and the cooling rate need to be controlled to avoid cracking or defects of the green body due to thermal stress.

[0054] The second step is to clean the (111) oriented SrTiO3 substrate by ultrasonic cleaning of the (111) oriented SrTiO3 substrate with anhydrous ethanol.

[0055] Specifically, the specific cleaning method in the second step is to use 60 ml of anhydrous ethanol for ultrasonic cleaning for 15 minutes, rinse with anhydrous ethanol for 15 seconds, and blow dry with a nitrogen gun to remove surface impurities and dirt.

[0056] The method of using anhydrous ethanol to ultrasonically clean the SrTiO3 substrate is as follows: A1, Preparation: Ensure that the operating area is well ventilated and wear appropriate personal protective equipment such as gloves and goggles.

[0057] A2, Cleaning chamber preparation: Select a suitable ultrasonic cleaning chamber to ensure that it can accommodate the SrTiO3 substrate to be cleaned and the substrate can be completely covered by the liquid. According to the instructions in the operating manual, preheat the cleaning chamber to a temperature suitable for the characteristics of the substrate and contaminants to ensure the best cleaning effect.

[0058] A3, Solution preparation: Pour high-purity anhydrous ethanol into the cleaning chamber. Due to its high purity, it can ensure the cleaning effect and substrate safety.

[0059] A4, Substrate placement: Check and ensure that the surface of the SrTiO3 substrate is clean and intact, and then place it in the cleaning chamber.

[0060] A5, Ultrasonic cleaning: Start the ultrasonic cleaning machine and set the cleaning time to about 15 minutes. The ultrasonic power can be adjusted appropriately according to the actual situation. The ultrasonic oscillation effect is used to remove pollutants on the substrate surface.

[0061] A6, post-cleaning treatment: After cleaning, stop the ultrasonic cleaning machine, take out the substrate, rinse it with pure anhydrous ethanol to remove the residual cleaning agent, and then use a nitrogen gun to generate a dry air flow to blow dry the substrate thoroughly.

[0062] In the third step, take out the SrTiO3 substrate, stick it on the sample stage of the laser pulse deposition instrument, put the sample stage into the sample delivery chamber, and evacuate the growth chamber and the sample delivery chamber to 5×10 -6 mbar, the sample stage is sent from the sample delivery chamber into the growth chamber.

[0063] It should be noted that the (111) oriented SrTiO3 substrate used is strontium titanate, a compound with a perovskite structure (ABO3 type), in which the A position is a Sr²⁺ ion and the B position is a Ti 4 ⁺ ions. It has a series of excellent physical properties, including high dielectric constant, low dielectric loss, good optical properties and thermal stability. For cubic SrTiO3, the (111) orientation means that during the growth process, the crystal grows and arranges along the direction of the (111) crystal plane in crystallography, so that the surface of the substrate is parallel to the (111) crystal plane. The SrTiO3 in the example is a product obtained by cutting, grinding and polishing a single crystal. It has a complete crystal structure, a high dielectric constant, a flat surface, and good chemical stability in common chemical environments. It can withstand a certain degree of acid and alkali corrosion, ensuring that the performance of the substrate will not be significantly affected by chemical factors during various preparation and application processes.

[0064] The sample stage is used to carry the substrate. It is a part of the laser pulse deposition instrument. It is an alloy support with a square ceramic plate in the center. The SrTiO3 substrate is attached to one side of the ceramic plate, and the other side is used to receive laser heating. The sample stage is placed on the specially adapted sample delivery rod in the sample delivery chamber, and then the sample delivery chamber is closed and the molecular pump connected to the sample delivery chamber is turned on to evacuate the sample. At the same time, the channel between the growth chamber connected to the sample delivery chamber remains closed, and the growth chamber always maintains 5×10 -6 mbar vacuum. When the vacuum degree of the sample delivery chamber reaches 5×10 -6 mbar, the passage between the sample delivery chamber and the growth chamber is opened, the sample stage is delivered into the growth chamber by the sample delivery rod, and fixed on the device carrying the sample stage in the growth chamber, and then the sample delivery rod is retracted to close the passage between the sample delivery chamber and the growth chamber.

[0065] The fourth step is to heat the SrTiO3 substrate to 750°C at a rate of 5°C / min, and use a baffle to separate the target and the substrate. When the temperature reaches 350°C, introduce the reaction gas O2 to make the gas pressure in the growth chamber reach 5mtorr.

[0066] Specifically, when heating the SrTiO3 substrate in the fourth step, a laser is used to heat the substrate. The laser power emitted by the laser is adjusted to increase the laser energy. The laser is focused on the back of the ceramic piece on the sample stage. The ceramic piece on the sample stage is heated to transfer heat to the substrate, thereby achieving the purpose of heating. At the same time, infrared rays are emitted on the ceramic piece to detect the temperature for temperature monitoring. The purpose of using a baffle to separate the target material and the substrate is to prevent the sputtering plume from reaching the substrate during the pre-sputtering process and affecting normal deposition.

[0067] Furthermore, SrTiO3 may undergo crystal phase transformation at different temperatures. Heating the temperature to 750°C at a rate of 5°C / min can avoid the substrate from undergoing an unexpected phase transformation to a certain extent. If the temperature is raised too quickly, it may cause excessive stress inside the substrate, triggering a phase transformation, affecting the performance of the substrate and its bonding with the film; while heating too slowly will affect production efficiency.

[0068] It should be noted that O2, referred to as oxygen, is the gaseous form of oxygen in the periodic table at room temperature and pressure. Oxygen is a colorless, tasteless, odorless gas that is widely present in nature. It is the second largest component in the air, accounting for about 21%, second only to nitrogen. During the heating stage of the laser pulse deposition ferroelectric film experiment, the introduction of oxygen has the following main effects: Cleaning the substrate: At high temperatures, oxygen can react with impurities such as hydrocarbons on the substrate surface to produce volatile substances such as carbon dioxide and water, achieving a cleaning effect. At the same time, it can also slightly etch the substrate surface to remove unevenness and defects, making the substrate surface smoother, which is conducive to the uniform growth of subsequent ferroelectric thin films.

[0069] Optimize substrate state: Oxygen can change the chemical state and physical properties of the substrate surface, making the atomic arrangement more orderly and the surface energy more suitable. For example, an oxide layer is formed on the surface of the metal substrate to stabilize the surface, enhance the lattice matching and chemical bonding with the ferroelectric film, and improve the binding force between the two. In addition, by adjusting the active sites on the substrate surface, the adsorption and reaction of the ferroelectric film precursor are in the best state.

[0070] Pre-reaction and formation of buffer layer: Oxygen will pre-react with elements or impurities in the ferroelectric material, oxidizing low-valent metal ions to high-valent states and adjusting the chemical composition. The reaction may also form a buffer layer on the substrate surface, alleviating the lattice mismatch and thermal stress between the film and the substrate, reducing the internal stress of the film, and improving stability.

[0071] Create a suitable atmosphere: Establish an oxygen-rich environment in the chamber in advance to provide stable conditions for chemical reactions during deposition and ensure that the chemical composition and crystal structure of the film meet the standards.

[0072] Step 5: Set the laser power density of the laser in the laser pulse deposition instrument to 1.5 - 2 J / cm² and the repetition frequency to 2 Hz. First, pre-sputter the HLO target for 2000 pulses, and then pre-sputter the LSMO target for 2000 pulses.

[0073] Among them, laser pulse deposition (PLD) is a vacuum thin film growth technology that uses high-power laser pulses to bombard the target material to melt, evaporate and ionize the material from the target target surface. This "ablation" will produce an instantaneous, highly luminous plasma plume, which quickly expands away from the surface, placing the substrate for the deposited growth material in a suitable position in advance, allowing the plume to reach the substrate for deposition and growth to form a thin film. Its advantages include the ability to precisely control the composition, accurately transfer the target material composition to the film, ensure the accuracy of complex chemical composition and stoichiometric ratio, and prepare high-quality thin films with good crystallinity, high flatness, and strong bonding with the substrate. It is also applicable to a wide range of materials, covering almost all materials such as metals, semiconductors, ceramics, polymers, etc. It is also easy to achieve multilayer film and heterogeneous structure preparation, providing strong support for the research and development of new materials and devices.

[0074] The laser power density of 1.5 - 2J / cm² can provide the target with just the right amount of energy. If the energy is too low, the target cannot be fully evaporated and ionized to form a high-quality plasma plume, which will result in a slow deposition rate and difficulty in film growth; if the energy is too high, the target may be over-evaporated and sputtered, causing damage to the target surface, and the energy of the particles in the plasma plume may be too high, which may damage the structure and performance of the film when deposited on the substrate surface.

[0075] The repetition frequency of 2Hz is to control the deposition rate and thus improve the film quality. 2Hz means that 2 laser pulses act on the target material per second. Together with the power density, it can accurately control the sputtering and deposition amount of the target material per unit time, so that the film grows at an appropriate rate. A deposition rate that is too slow will affect the experimental efficiency, while a deposition rate that is too fast may lead to problems such as uneven film growth and poor crystal quality.

[0076] Pre-sputtering is the preparation work before the formal growth sputtering. By using the plasma generated by high-energy ions or laser pulses, the target surface can be cleaned, and dust, impurities and oxide layers that may be adsorbed during the installation process can be removed, so that the target can participate in the subsequent thin film deposition process with a clean surface, thereby avoiding the incorporation of impurities into the film and ensuring the purity and quality of the film. The target surface can also be activated to make the atoms on the target surface more active. This is because the energy input during the pre-sputtering process breaks the relatively stable state of the atoms on the target surface and increases the activity of the surface atoms. The activated target surface is more conducive to reacting or combining with the particles in the plasma during the formal deposition, thereby improving the deposition efficiency and quality of the film and helping the film to grow and crystallize better. Pre-sputtering also plays a role in stabilizing the sputtering process. Pre-sputtering stabilizes the interaction process between the laser and the target, making the plasma generation and transmission processes more stable. In this way, when the film is formally deposited later, it can ensure that the sputtered particles have more consistent energy and quantity, thereby improving the uniformity and consistency of the film growth, which is conducive to obtaining a film with stable quality.

[0077] The purpose of pre-sputtering the HLO target first and then the LSMO target is to keep the environmental changes during growth as small as possible. Since the formal growth process is to grow the LSMO electrode buffer layer first, the LSMO target pre-sputtering and the LSMO electrode buffer layer are carried out continuously, which is conducive to the relatively stable deposition environment.

[0078] Step 6. After the pre-sputtering is completed, the baffle is opened. After the temperature is heated to 750°C, the amount of O2 introduced is increased to make the gas pressure in the growth chamber reach 100mtorr. The LSMO layer is first deposited on the substrate, and the number of sputtering is set to 3000pulse. After the sputtering is completed, the temperature is raised to 780°C at a rate of 5°C / min, and the HLO layer is deposited, and the number of sputtering is set to 2000pulse. After the deposition is completed, the sample is cooled to room temperature at a rate of 5°C / min. During the cooling process, the O2 pressure is constant at 100mtorr. After cooling to room temperature, the O2 introduction is cut off. After the molecular pump in the growth chamber extracts the residual O2, the growth chamber and the sample delivery chamber are connected, and the sample stage is taken out to the sample delivery chamber. After the channel between the growth chamber and the sample delivery chamber is cut off, the vacuum in the sample delivery chamber is broken and the sample stage is taken out.

[0079] Specifically, LSMO is grown at 750°C because LSMO has a perovskite structure. At a temperature of about 750°C, atoms have enough energy to diffuse and rearrange, which is conducive to the formation of a complete and ordered perovskite crystal structure. This temperature can cause atoms such as lanthanum (La), strontium (Sr), manganese (Mn) and oxygen (O) in LSMO to be arranged in specific lattice positions, thereby obtaining good crystal quality and electrical properties.

[0080] Furthermore, the growth of HLO at 780°C is due to the fact that hafnium oxide has multiple crystal phases, and different crystal phases correspond to different physical properties. Around 780°C, hafnium oxide is conducive to forming a crystal phase with ferroelectricity, such as orthorhombic phase or tetragonal phase. This crystal phase transition is crucial to achieving the ferroelectric properties of hafnium oxide films, which can make the film have good polarization characteristics and hysteresis loops.

[0081] Furthermore, during the deposition process, O2 is introduced to 100 mtorr. First, the stoichiometric ratio of the film can be stabilized. During the deposition process, the introduction of oxygen helps to ensure that the metal elements La, Sr, and Mn in the LSMO electrode buffer layer, and the metal elements Hf and La in the ferroelectric HLO film reach the correct stoichiometric ratio with oxygen elements. If the oxygen supply is insufficient, oxygen vacancies may appear in the electrode buffer layer and the HLO film, causing the chemical composition of the HLO film to deviate from the ideal, thereby affecting its ferroelectric properties. Secondly, a suitable oxygen atmosphere is essential for the formation of a good crystal structure for ferroelectric films. Oxygen participates in the chemical reactions during the deposition process, which helps atoms to arrange according to a specific lattice structure and promotes the formation of a ferroelectric phase with good crystallinity. In particular, the La element is a variable valence element, and the presence of La in the crystal structure 2+ with La 3+ Two valence states, if oxygen is insufficient, La 2+ Too much can easily affect the crystal structure, causing the ferroelectric phase to transition to the non-ferroelectric phase.

[0082] Furthermore, the growth times of the LSMO electrode buffer layer and the HLO film are set to regulate the film thickness, and the thickness of the HLO film obtained in this way is about 10 nm.

[0083] After the controlled deposition is completed, the sample is cooled to room temperature at a rate of 5℃ / min. First, it is to stabilize the crystal structure: slow cooling helps the crystal structure of the film and substrate to maintain the specific phase and orientation formed during the deposition process. Cooling at a rate of 5℃ / min can give atoms enough time to relax and adjust, maintain the formed crystal structure during the cooling process, and avoid crystal structure distortion or phase transition caused by rapid cooling, thereby ensuring that the material has the expected physical and chemical properties. Secondly, it is to reduce stress-induced phase change: rapid cooling may produce large thermal stress inside the sample, which may induce undesirable phase changes in the crystal structure. When cooling slowly, thermal stress can be released more evenly, reducing the possibility of stress-induced phase change and making the crystal structure of the sample more stable. Finally, it is to prevent the film from falling off from the substrate or generating additional stress: HLO film and STO substrate have different thermal expansion coefficients. During the cooling process, if the cooling rate is too fast, the stress generated by the difference in thermal expansion between the two may exceed the interface bonding force, causing the film to fall off from the substrate. Slow cooling can give the film and substrate more time to adapt to the difference in thermal expansion, reduce interfacial stress, and ensure good bonding between the film and substrate.

[0084] In the seventh step, a circular mask with a diameter of 30 μm was covered on the sample surface and fixed on the magnetron sputtering sample stage. The sample stage was placed in the sputtering chamber and the background vacuum was pumped to 5×10 -5 torr, sputtered Pt target for 10 min, and formed a circular top electrode on the sample surface as the metal top electrode of the capacitor. The ferroelectric properties of the film were tested with a ferroelectric tester.

[0085] It should be noted that magnetron sputtering is a type of physical vapor deposition (PVD) technology that forms a thin film by converting solid materials into gaseous atoms or molecules and depositing them on the surface of the substrate to be coated. After the sample is fixed, the sample stage is carefully placed in the sputtering chamber.

[0086] The sputtering chamber is the core equipment of magnetron sputtering, which is mainly composed of vacuum chamber, target material, substrate holder and sputtering source. To ensure the quality of the film, the background vacuum of the sputtering chamber must be pumped to 5×10 -5The vacuum chamber plays a key role in sealing, which can prevent the film from reacting with air or impurities during the film formation process. The gas inside the vacuum chamber is extracted by the exhaust system to maintain a low-pressure environment. The target material is Pt, which is the raw material for forming the film and will release atoms under the bombardment of high-energy particles. The substrate holder is used to carry the sample, which is the substrate for the subsequent formation of the film. The sputtering source activates the target material in a specific way to cause it to release atoms.

[0087] When the sputtering chamber reaches the required vacuum, the Pt target is sputtered for 10 minutes. During the sputtering process, the sputtering source works to release Pt particles from the target. These particles are deposited on the sample surface in the form of sputtering flow in a vacuum environment, gradually forming a circular top electrode, which will serve as the metal top electrode of the capacitor.

[0088] Specifically, in the seventh step, the circular top electrode is formed with a thickness of 40 nm and a diameter of 30 μm.

[0089] Example 1 A circular mask with a diameter of 30 μm is covered on the sample surface, and Pt with a thickness of 40 nm and a diameter of 30 μm is sputtered as a circular top electrode. Then, a Pt / HLO / LSMO / STO capacitor structure having a Pt top electrode and a LSMO bottom electrode is processed according to Figure 2 The steps shown are to expose the bottom electrode, cover the exposed portion with silver paste, and then heat it at 70° C. for 5 minutes on a heating table to dry the ethanol in the silver paste.

[0090] Completed as Figure 2 After the steps, the ferroelectric properties of the film are tested using a ferroelectric tester.

[0091] The XRD q-2q spectrum of the sample is as follows Figure 4 As shown in the figure, the (111) diffraction peak of the HLO orthorhombic phase at 2q = 29.7° was observed, and no characteristic peak of the monoclinic phase appeared, indicating that the film is mainly an orthorhombic phase. The XRD q-2q spectrum of the {111} diffraction of the sample is shown in Figure 5 As shown in the figure, the 2q angle of the out-of-plane (111) direction is smaller than that of the in-plane {111} plane, indicating that the out-of-plane lattice constant is larger than that of the in-plane, and the HLO film has a rhombus deformation. Figure 6 As shown in the figure, the surface morphology of the film is observed. The root mean square roughness of the selected area of ​​3×3μm² is less than 120pm, and the surface quality is high. The hysteresis loop tested by the ferroelectric tester is shown in the figure below. Figure 7 As shown, the remnant polarization P r 13mC / cm², coercive field E c is about 2.1 MV / cm. The current density in the film is Figure 8 As shown, the current is 10-6 A / cm -2 Fatigue durability test Fig. 9 As shown, a triangular cyclic pulse with an amplitude of 5V (greater than 1.5 times the coercive field) was used for 10 9 After a cycle, more than 80% of the initial polarization is maintained. The polarization state diagrams under different cycle periods are shown in Fig.10 shown.

[0092] Example 2

[0093] First, a buffer layer (La 0.67 Sr 0.33 MnO3), and then La-doped hafnium oxide-based ferroelectric thin film layer was epitaxially grown on the surface of the buffer layer to obtain La-doped hafnium oxide-based ferroelectric thin film. The La doping concentration of La-doped hafnium oxide is 5 at%. The thickness of La-doped hafnium oxide-based ferroelectric thin film is 15nm. Further prepare Pt top electrode, obtain capacitor structure, and conduct ferroelectric test and XRD test. The XRD results show that HLO has obvious (111) orthorhombic phase, and the residual polarization P r About 11mC / cm², coercive field E c About 1.9 MV / cm. A triangular cyclic pulse with an amplitude of 5 V (greater than 1.5 times the coercive field) was used for 10 9 After one cycle, about 74% of the initial polarization is maintained.

[0094] Example 3

[0095] First, a buffer layer (La 0.67 Ca 0.33 MnO3 (LCMO)), and then epitaxially grow a La-doped hafnium oxide-based ferroelectric thin film layer on the surface of the buffer layer to obtain a La-doped hafnium oxide-based ferroelectric thin film. The La doping concentration of the La-doped hafnium oxide is 2 at%. The thickness of the La-doped hafnium oxide-based ferroelectric thin film is 10 nm. The specific experimental steps are: (1) La-doped hafnium oxide-based target and buffer layer target are sintered by solid phase reaction method, and the target is placed in the target chamber in the growth chamber of the laser pulse deposition instrument; (2) Fixing the (111) oriented perovskite substrate on the sample stage, and placing the sample stage into the sample delivery chamber, evacuating the growth chamber and the sample delivery chamber, and then transferring the sample stage from the sample delivery chamber into the growth chamber; (3) Raise the temperature of the (111) oriented perovskite substrate to 720°C and use a baffle to separate the target material and the substrate; when the temperature reaches 320°C, introduce O2 to make the pressure in the growth chamber reach 3 mtorr; (4) Pre-sputtering of La-doped hafnium oxide-based target and buffer layer target; (5) After the pre-sputtering, open the baffle, and when the temperature is heated to 720°C, increase the amount of O2 introduced to make the gas pressure in the growth chamber reach 90 mtorr. First, deposit a buffer layer on the substrate, and set the sputtering number to 2500 pulses. After the sputtering is completed, raise the temperature to 750°C and deposit a La-doped hafnium oxide-based thin film layer, and set the sputtering number to 3000 pulses. After the deposition is completed, the sample is cooled to room temperature, and the O2 pressure is maintained at 90 mtorr during the cooling process. A La-doped hafnium oxide-based ferroelectric thin film is obtained.

[0096] The Au top electrode was further prepared to obtain the capacitor structure, and ferroelectric tests and XRD tests were performed. The XRD results showed that HLO had an obvious (111) orthorhombic phase and the residual polarization P r About 9mC / cm², coercive field E c About 2.5MV / cm. A triangular cyclic pulse with an amplitude of 5V (greater than 1.5 times the coercive field) was used for 10 9 After one cycle, about 63% of the initial polarization is maintained.

[0097] Example 4

[0098] First, a buffer layer (La 0.5 Sr 0.5 MnO3), and then epitaxially grow a La-doped hafnium oxide-based ferroelectric thin film layer on the surface of the buffer layer to obtain a La-doped hafnium oxide-based ferroelectric thin film. The La doping concentration of the La-doped hafnium oxide is 8 at%. The thickness of the La-doped hafnium oxide-based ferroelectric thin film is 20 nm. The specific experimental steps are: (1) La-doped hafnium oxide-based target and buffer layer target are sintered by solid phase reaction method, and the target is placed in the target chamber in the growth chamber of the laser pulse deposition instrument; (2) Fixing the (111) oriented perovskite substrate on the sample stage, and placing the sample stage into the sample delivery chamber, evacuating the growth chamber and the sample delivery chamber, and then transferring the sample stage from the sample delivery chamber into the growth chamber; (3) Heating the (111) oriented perovskite substrate to 780°C and using a baffle to separate the target material and the substrate; when the temperature reaches 380°C, introducing O2 to make the pressure in the growth chamber reach 7 mtorr; (4) Pre-sputtering of La-doped hafnium oxide-based target and buffer layer target; (5) After the pre-sputtering, open the baffle, and when the temperature is heated to 780°C, increase the amount of O2 introduced to make the gas pressure in the growth chamber reach 110 mtorr. First, deposit a buffer layer on the substrate, and set the sputtering number to 3500 pulses. After the sputtering is completed, raise the temperature to 810°C and deposit a La-doped hafnium oxide-based thin film layer, and set the sputtering number to 4000 pulses. After the deposition is completed, the sample is cooled to room temperature, and the O2 pressure is maintained at 110 mtorr during the cooling process. A La-doped hafnium oxide-based ferroelectric thin film is obtained.

[0099] The Ag top electrode was further prepared to obtain the capacitor structure, and ferroelectric tests and XRD tests were performed. The XRD results showed that HLO had an obvious (111) orthorhombic monoclinic phase and a residual polarization P r About 14mC / cm², coercive field E c About 2.8 MV / cm. A triangular cyclic pulse with an amplitude of 6 V (greater than 1.5 times the coercive field) was used for 10 9 After one cycle, about 59% of the initial polarization is maintained.

[0100] Example 5

[0101] First, a buffer layer (La 0.67 Sr 0.33 MnO3), and then epitaxially grow a La-doped hafnium oxide-based ferroelectric thin film layer on the surface of the buffer layer to obtain a La-doped hafnium oxide-based ferroelectric thin film. The La doping concentration of the La-doped hafnium oxide is 2 at%. The thickness of the La-doped hafnium oxide-based ferroelectric thin film is 20 nm. The specific experimental steps are: (1) La-doped hafnium oxide-based target and buffer layer target are sintered by solid phase reaction method, and the target is placed in the target chamber in the growth chamber of the laser pulse deposition instrument; (2) Fixing the (111) oriented perovskite substrate on the sample stage, and placing the sample stage into the sample delivery chamber, evacuating the growth chamber and the sample delivery chamber, and then transferring the sample stage from the sample delivery chamber into the growth chamber; (3) Heating the (111) oriented perovskite substrate to 750°C and using a baffle to separate the target material and the substrate; when the temperature reaches 350°C, introducing O2 to make the pressure in the growth chamber reach 5 mtorr; (4) Pre-sputtering of La-doped hafnium oxide-based target and buffer layer target; (5) After the pre-sputtering, the baffle is opened. After the temperature is heated to 750°C, the O2 flow rate is increased to make the gas pressure in the growth chamber reach 100 mtorr. A buffer layer is first deposited on the substrate, and the sputtering number is set to 3000 pulses. After the sputtering is completed, the temperature is raised to 780°C, and a La-doped hafnium oxide-based thin film layer is deposited, and the sputtering number is set to 4000 pulses. After the deposition is completed, the sample is cooled to room temperature, and the O2 pressure is maintained at 100 mtorr during the cooling process. A La-doped hafnium oxide-based ferroelectric thin film is obtained.

[0102] A Pt electrode was then coated thereon according to the process and apparatus of Example 1 to prepare a capacitor structure, and a ferroelectric test and an XRD test were performed. A HLO ferroelectric film with a thickness of about 20 nm was obtained, and the XRD results showed that the HLO was an orthorhombic phase (111) and the residual polarization P r 10mC / cm², coercive field E c About 2.5 MV / cm. A triangular cyclic pulse with an amplitude of 6 V (greater than 1.5 times the coercive field) was used for 10 9 After one cycle, about 60% of the initial polarization is maintained.

[0103] Example 6

[0104] The SrTiO3 (111) oriented substrate was cleaned according to the method of Example 1, and the target material was pre-sputtered. During the film growth stage, the buffer layer La was sputtered with the same 3000 pulses. 0.67 Sr 0.33 MnO3, sputtering growth of HLO layer for 4000 pulses, to obtain La-doped hafnium oxide-based ferroelectric film. The La doping concentration of La-doped hafnium oxide is 5 at%. The thickness of La-doped hafnium oxide-based ferroelectric film is 20 nm. The specific steps are: (1) La-doped hafnium oxide-based target and buffer layer target are sintered by solid phase reaction method, and the target is placed in the target chamber in the growth chamber of the laser pulse deposition instrument; (2) Fix the cleaned (111) oriented perovskite substrate on the sample stage, place the sample stage into the sample delivery chamber, and evacuate the growth chamber and the sample delivery chamber to 5×10 -6 mbar, the sample stage is sent from the sample delivery chamber into the growth chamber; (3) The (111) oriented perovskite substrate was heated to 750°C at a rate of 5°C / min, and a baffle was used to separate the target material and the substrate; when the temperature reached 350°C, O2 was introduced to make the pressure in the growth chamber reach 5 mtorr; (4) Pre-sputtering of La-doped hafnium oxide-based target and buffer layer target; (5) After the pre-sputtering is completed, the baffle is opened. After the temperature is heated to 750°C, the O2 flow rate is increased to make the gas pressure in the growth chamber reach 100 mtorr. A buffer layer is first deposited on the substrate, and the sputtering number is set to 3000 pulses. After the sputtering is completed, the temperature is raised to 780°C at a rate of 5°C / min to deposit a La-doped hafnium oxide-based thin film layer, and the sputtering number is set to 4000 pulses. After the deposition is completed, the sample is cooled to room temperature at a rate of 5°C / min. During the cooling process, the O2 pressure is maintained at 100 mtorr. A La-doped hafnium oxide-based ferroelectric thin film is obtained.

[0105] According to the process and apparatus of Example 1, a Pt electrode was covered on the HLO film to prepare a capacitor structure, and a ferroelectric test and an XRD test were performed. Finally, a HLO film with a thickness of about 20 nm was obtained. The XRD results showed that the HLO was an orthorhombic phase (111) and the residual polarization P r About 10mC / cm², coercive field E c About 1.7 MV / cm. A triangular cyclic pulse with an amplitude of 5 V (greater than 1.5 times the coercive field) was used for 10 9 After one cycle, about 68% of the initial polarization is maintained.

[0106] Comparative Example 1 Prepare Hf according to the method of Example 1 0.5 Zr 0.5 O2 target. Clean the SrTiO3 (111) oriented substrate according to the method in Example 1, pre-sputter the target, and in the film growth stage, maintain the same growth conditions and grow and sputter the same 3000 pulse La 0.67 Sr 0.33 MnO3, sputtering growth of HZO layer for 2000 pulses. According to the process and apparatus of Example 1, Pt electrode was covered on the HZO film, capacitor structure was prepared, and ferroelectric test and XRD test were performed. A HZO ferroelectric film with a thickness of about 10nm was obtained. No HZO phase was observed in the XRD results. Through reciprocal space scanning and scanning tunneling microscope (STEM) analysis, it can be found that HZO does not have a pure orientation, but an inclined epitaxial, and there are three crystals with different angles relative to the plane normal direction. Its residual polarization P r About 14mC / cm², coercive field E c About 3.8MV / cm. After 10 9 After one cycle, about 20% of the initial polarization is maintained.

[0107] Comparative Example 2 The SrTiO3 (001) oriented substrate was cleaned according to the method of Example 1, and the target was pre-sputtered. During the film growth stage, the same growth conditions were maintained, and the same 3000 pulse La was sputtered. 0.67 Sr 0.33 MnO3, sputtering growth of HLO layer for 2000 pulses. Pt electrode was covered on HLO film according to the process and apparatus of Example 1, capacitor structure was prepared, ferroelectric test and XRD test were carried out. Finally, HLO film with thickness of about 10nm was obtained. The XRD results showed that HLO had orthorhombic phase (111) and monoclinic phase (-111), and remanent polarization P r About 14mC / cm², coercive field E c About 4MV / cm. A triangular cyclic pulse with an amplitude of 7V (greater than 1.5 times the coercive field) was used for 10 9 After one cycle, the initial polarization is maintained at about 18%.

Claims

1. A La-doped hafnium oxide-based ferroelectric thin film, characterized in that: La-doped hafnium oxide-based ferroelectric thin films have a single (111) oriented orthorhombic phase structure.

2. The La-doped hafnium oxide-based ferroelectric thin film according to claim 1, characterized in that: The La doping concentration of La-doped hafnium oxide is 2~8 at%.

3. The La-doped hafnium oxide-based ferroelectric thin film according to claim 1, characterized in that: The thickness of the La-doped hafnium oxide-based ferroelectric film is 10nm~20nm.

4. A La-doped hafnium oxide-based ferroelectric film capacitor, characterized in that: It includes a buffer layer, a La-doped hafnium oxide-based ferroelectric film, and a metal top electrode; the buffer layer is provided with a La-doped hafnium oxide-based ferroelectric film, and the La-doped hafnium oxide-based ferroelectric film is provided with a metal top electrode.

5. The La-doped hafnium oxide-based ferroelectric thin film capacitor according to claim 4, characterized in that: The buffer layer is La (1-x) A x MnO3, 0<x<1, A is a divalent metal ion.

6. The La-doped hafnium oxide-based ferroelectric thin film capacitor according to claim 4, characterized in that: The thickness of the buffer layer is 15-20 nm, and the thickness of the metal top electrode is 30-50 nm.

7. A method for preparing the La-doped hafnium oxide-based ferroelectric thin film according to claim 1, characterized in that: First, a buffer layer with consistent orientation is epitaxially grown on a (111) oriented perovskite substrate, and then a La-doped hafnium oxide-based ferroelectric thin film layer is epitaxially grown on the surface of the buffer layer to obtain a La-doped hafnium oxide-based ferroelectric thin film.

8. The method for preparing the La-doped hafnium oxide-based ferroelectric thin film according to claim 7, characterized in that: The (111) oriented perovskite substrate includes SrTiO3, GdScO3 or LaAlO3.

9. The method for preparing the La-doped hafnium oxide-based ferroelectric thin film according to claim 7, characterized in that: The following steps are involved: (1) La-doped hafnium oxide-based target and buffer layer target are sintered by solid phase reaction method, and the target is placed in the target chamber in the growth chamber of the laser pulse deposition instrument; (2) Fixing the (111) oriented perovskite substrate on the sample stage, and placing the sample stage into the sample delivery chamber, evacuating the growth chamber and the sample delivery chamber, and then transferring the sample stage from the sample delivery chamber into the growth chamber; (3) Raise the temperature of the (111) oriented perovskite substrate to 720-780°C and use a baffle to separate the target material and the substrate; when the temperature reaches 320-380°C, introduce O2 to make the pressure in the growth chamber reach 3-7 mtorr; (4) Pre-sputtering of La-doped hafnium oxide-based targets and buffer layer targets; (5) After the pre-sputtering is completed, the baffle is opened. After the temperature is heated to 720~780℃, the O2 flow rate is increased to make the gas pressure in the growth chamber reach 90~110mtorr. The buffer layer is first deposited on the substrate, and the sputtering times are set to 2500~3500pulse. After the sputtering is completed, the temperature is raised to 750~810℃, and the La-doped hafnium oxide-based thin film layer is deposited, and the sputtering times are set to 2000~4000pulse. After the deposition is completed, the sample is cooled to room temperature, and the O2 pressure is maintained at 90~110mtorr during the cooling process. A La-doped hafnium oxide-based ferroelectric thin film is obtained.

10. A method for preparing the La-doped hafnium oxide-based ferroelectric film capacitor according to claim 4, characterized in that: First, a buffer layer with consistent orientation is epitaxially grown on a (111) oriented perovskite substrate, and then a La-doped hafnium oxide-based ferroelectric thin film layer is epitaxially grown on the surface of the buffer layer. A mask plate is covered on the surface of the La-doped hafnium oxide-based ferroelectric thin film layer, and a metal target is magnetron sputtered to form a metal top electrode, thereby obtaining a La-doped hafnium oxide-based ferroelectric thin film capacitor.

Citation Information

Patent Citations

  • Semiconductor device and manufacturing method thereof

    CN109727870A

  • Thin-film structure and semiconductor device comprising the same

    US20230282389A1

Cited By

  • Ferroelectric film with two-dimensional layered electrode and preparation method thereof

    CN120568774A

  • Epitaxial hafnium oxide-based ferroelectric capacitor and atomic layer deposition preparation method thereof

    CN121240468A